Design of a Simple Pyrolysis Reactor for Plastic Waste Conversion into Liquid Fuel using Biomass as Heating Source - Aditya Kurniawan; Bambang Sugiarto; Andri Perdana (Eksergi, 2020)
A design that emphasizes simplicity and cost-effectiveness is applied to the plastic pyrolysis reaction system to produce liquid fuel. The reactor is fabricated from the waste refrigerant tank. The energy source for pyrolysis is generated by the combustion of biomass pellets. Forced convection by an electric blower is utilized to enhance the combustion efficiency and thus increase the heating rate with the overall average temperature at 412 °C. The coiled pipe is employed as a condenser system with water as its cooling media. The quantity of liquid product is measured for a different mass of PET-type plastic waste feed, with a maximum value of 17.7% w/w of feed mass is obtained. The physical characteristic of the liquid product is then analyzed using standard methods. It is found that its characteristics have approached the specification of commercial liquid fuel in the domestic market, with a liquid specific gravity of 0.776 and a heating value of 46 MJ/kg.